2008
DOI: 10.1016/j.jsb.2008.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Forming nacreous layer of the shells of the bivalves Atrina rigida and Pinctada margaritifera: An environmental- and cryo-scanning electron microscopy study

Abstract: A key to understanding control over mineral formation in mollusk shells is the microenvironment inside the pre-formed 3-dimensional organic matrix framework where mineral forms. Much of what is known about nacre formation is from observations of the mature tissue. Although these studies have elucidated several important aspects of this process, the structure of the organic matrix and the microenvironment where the crystal nucleates and grows are very difficult to infer from observations of the mature nacre. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
1
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(122 citation statements)
references
References 29 publications
3
115
1
3
Order By: Relevance
“…It is known that fresh nacre substrate is usually covered by a thin organic layer [27][28][29], which can be eliminated by 5% NaClO solution. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that fresh nacre substrate is usually covered by a thin organic layer [27][28][29], which can be eliminated by 5% NaClO solution. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fresh nacre surface is usually covered by a sheet of organic matrix [27][28][29], which is composed of insoluble matrix and soluble matrix [11]. Previous reports show that ACC exists in nacre and is stabilized by soluble organic matrix [21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…This amphiphilic property could be an important driving force for selforganisation, resulting in the observed layered organic sheets. The modified chitin fraction might form the interface between the chitin core and the interlamellar matrix surface, which is in contact with the proposed hydrophobic silk-like gel [49,[150][151][152][153] between the interlamellar layers. 2 In 2009, Checa et al showed TEM images of extracellular vesicles, fusing with the surface of the interlamellar matrix sheets at the mantle side of gastropods [154].…”
Section: Formation Of the Interlamellar Matrixmentioning
confidence: 99%
“…The organic matters in the nacreous layer are distributed between the layers of aragonite crystals or wrapped around nanoscale aragonite crystals continuously and in parallel [35][36][37][38]. The development of modern molecular biology encourages people to explore the biomineralization mechanism and nacreous layer's formation mechanism from the perspective of genetic control [39,40].…”
Section: Discussionmentioning
confidence: 99%